Pengaruh Bi Rate, Exchange Rate(Idr/Usd), Dan Inflasi Terhadap Indeks Saham Syariah Yang Tercatat di JII Di Masa Pandemi Covid-19 Tahun 2020. - Abdul Majid; Ronny Malavia Mardani; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine and analyze the effect of the BI Rate, Exchange Rate, and Inflation on the Islamic stock index listed at JII during the COVID-19 pandemic. This research is an explanatory research type, with a quantitative approach. The analytical method used is multiple linear regression analysis. The sample used in this study using purposive sampling technique obtained 30 companies.The results of this study indicate that partially there is no significant effect between the BI Rate on the stock index, the Exchange Rate has a significant effect on the stock index and inflation has no effect on the stock index. Keywords: BI Rate, Exchange Rate, Inflation and stock index